Television Advertising As An Artwork In Representing National Identity - Dewi, Alit Kumala; I Nyoman, Artayasa (Institut Seni Indonesia Denpasar, 2019)
Advertising has a dual role, one side of the advertising is a medium of information to convey messages, both commercial and non-commercial to the audience, and the other side as artwork (applied art) with all its appeal. The priority for advertising is marketing and selling products or services. In its representation, advertising always uses any aesthetic elements, which in principle can potentially be a great attraction for the products or services offered. Concepts that are often represented in ad impressions include, social status, ideal image, lifestyle, identity, etc., which are displayed implicitly or explicitly. This study focuses on the representation of Indonesia’s national identity in the SGM formula milk television commercials. The purpose of the study is to provide a description and description so as to open up insights and knowledge in understanding how Indonesia’s national identity is represented in advertisements for SGM children’s formula milk. The method used is interpretive qualitative The results of the research, that the advertising of SGM formula milk as a work of applied art represents Indonesian national identity, which can be classified into three parts 1) Culture, Religion, Ethnicity of Indonesia; 2) Nusantara Territory (Enchantment of Indonesian and Urban Nature); 3) Characteristics of Indonesian Communities (Habits / Lifestyle) The characteristics of Indonesian society can be interpreted as a socialist and minimalist society. Based on the three classifications of the representation of Indonesia’s national identity, the most dominant part displayed in the SGM formula milk television commercials is the element of religion